2003
DOI: 10.1046/j.1524-4725.2003.29064.x
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Superficial Lymphatic Malformation: Report of a Case and Review of the Literature

Abstract: Superficial lymphatic malformations can develop in adults spontaneously without the presence of any predisposing condition. Because the majority of such late-onset malformations reported in the literature are localized lesions similar to the one in our patient, surgical removal with inclusion of subcutaneous tissue usually results in cure without recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Our results demonstrate that benign lymphangioendothelioma lacks expression of WT‐1, supporting it being a lymphatic vascular malformation. It must be noted that WT‐1 has also been negative in all tested lesions with lymphatic vascular differentiation, and the only exception was the case reported by Revelles et al Lymphatic malformations are usually congenital, but tardive onset has also been described . Recently, hobnail angioma, a vascular proliferation that usually develop in adults, was also proven to be a lymphatic malformation .…”
Section: Discussionmentioning
confidence: 96%
“…Our results demonstrate that benign lymphangioendothelioma lacks expression of WT‐1, supporting it being a lymphatic vascular malformation. It must be noted that WT‐1 has also been negative in all tested lesions with lymphatic vascular differentiation, and the only exception was the case reported by Revelles et al Lymphatic malformations are usually congenital, but tardive onset has also been described . Recently, hobnail angioma, a vascular proliferation that usually develop in adults, was also proven to be a lymphatic malformation .…”
Section: Discussionmentioning
confidence: 96%
“…Lymphangioma circumscriptum is the most common congenital lymphatic malformation, although its true incidence is unknown . Approximately 90% of lymphangioma circumscriptum cases manifest by age 2 years, and the remainder typically appear before age 30 years . Lymphangioma circumscriptum lesions function as a “closed system,” entirely separate from the normal lymphatic system .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of lymphangioma circumscriptum cases manifest by age 2 years, and the remainder typically appear before age 30 years . Lymphangioma circumscriptum lesions function as a “closed system,” entirely separate from the normal lymphatic system . During lymphatic development, abnormal cisterns with a muscular coating form in the subcutaneous tissue .…”
Section: Discussionmentioning
confidence: 99%
“…1 The highest incidence of lymphangioma is during infancy, and most appear by age 30, with very few cases reported in later life. 2 The condition affects males and females equally; it can be congenital or acquired, and the two are usually indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5,[8][9][10] A survey of 80 patients with cutaneous lymphangiomas showed that 75% of the lesions are cured with one surgical excision, and 13% with a second excision. 7 These cases involved lymphangioma of chest, thigh, buttock, neck and axilla; scrotal lymphangiomas were rare.…”
mentioning
confidence: 99%